Oxygen uptake kinetics during supra-maximal exercise: Mathematical modelling - Daniel Müller Hirai; Nilo Massaru Okuno; Luiz Augusto Buoro Perandini; Guilherme Morais Puga; Herbert Gustavo Simões; Fábio Yuzo Nakamura (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n1p43 Precise estimation of oxygen uptake kinetics parameters is essential to understand its control and/or limit uptake mechanisms. The purpose of the present study was to characterize the oxygen uptake kinetics responses during supramaximal cycle ergometer exercise using two modeling techniques. Eleven male subjects (age = 25.4 ± 4.9 years, height = 177.0 ± 4.0 cm, mass = 77.1 ± 11.3 kg, VO2max = 40.3 ± 6.3 mL.kg-1.min-1) performed a series of square- have exercise transitions to exhaustion at intensities equivalent to 100, 113, 133 and 153% of VO2max. The time constant of the primary component was estimated with an exponential and semi-logarithmic model, comparisons were made using repeated measures ANOVA and the Tukey post hoc tests, with statistical signifi cance accepted when p<0.05. In order to calculate the time constant by the semi-logarithmic model it is necessary to estimate oxygen demand, which was performed by means of a regression procedure. The exponential model resulted in lower values for the time constant (35.1 ± 8.0s; 32.5 ± 7.4s; 29.6 ± 11.3s; 25.3 ± 7.5s) compared to the semi-logarithmic model (107.9 ± 27.1s; 104.5 ± 24.3s; 114.1 ± 30.4s; 125.3 ± 24.9s) at all intensities. The observation of this confl icting oxygen uptake kinetics behavior depending upon which mathematical model is applied suggests that physiological inferences on the basis of parameters obtained during supra-maximal exercise should be made with caution.